Scripted-IMPROV: Interactive Improvisational Drama With Persons With Dementia-Effects on Engagement, Affect, Depression, and Quality of Life - Zeisel, John; Skrajner, Michael J; Zeisel, Evan B; Wilson, Miranda Noelle; Gage, Chris (American journal of Alzheimer's disease and other dementias, 2018)
Scripted-IMPROV (SI) is a nonpharmacological (ecopsychosocial) intervention that consists of semi-improvised drama performances specifically designed for persons with dementia (PWD). In this 12-site study, 178 PWD took part in the SI intervention. Levels of engagement/affect were assessed at baseline and again during SI performances; quality of life (via the Dementia Quality of Life scale) and depression (via the Geriatric Depression Scale-Short Form [GDS-SF]) were assessed at baseline and post-treatment. Positive forms of engagement/affect increased, while negative forms of engagement decreased. Regarding depression, for a subsample of 29 participants who scored in the depressed range on the GDS-SF at baseline, depressive symptoms were reduced at post-treatment. Although overall quality of life did not change, the increase in positive affect during SI suggests that quality of life was higher during the intervention itself. In conclusion, SI possesses the characteristics of a high-quality intervention for PWD and seems worthy of further investigation in future research.